2016
DOI: 10.1038/aps.2016.17
|View full text |Cite
|
Sign up to set email alerts
|

Polygalasaponin XXXII, a triterpenoid saponin from Polygalae Radix, attenuates scopolamine-induced cognitive impairments in mice

Abstract: Aim: Recent studies show that the extract of a Chinese herb Polygalae Radix exerts cognition-enhancing actions in rats and humans. The aim of this study was to characterize the pharmacological profiles of active compounds extracted from Polygalae Radix. Methods: Two fractions P3 and P6 and two compounds PTM-15 and polygalasaponin XXXII (PGS32) were prepared. Neuroprotective effects were evaluated in primary cortical neurons exposed to high concentration glutamate, serum deficiency or H 2 O 2 . Anti-dementia ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 37 publications
0
10
1
Order By: Relevance
“…PRE did not recover spatial memory dysfunction, in contrast to previous studies . This inconsistency may be due to differences in the animal models used.…”
Section: Discussioncontrasting
confidence: 83%
See 2 more Smart Citations
“…PRE did not recover spatial memory dysfunction, in contrast to previous studies . This inconsistency may be due to differences in the animal models used.…”
Section: Discussioncontrasting
confidence: 83%
“…Li et al . described ameliorative effects of an ingredient of Polygalae radix on cognitive impairment in a transgenic Alzheimer disease model , and the four other aforementioned studies showed that ingredients or extracts of Polygalae radix improved scopolamine‐induced cognitive impairment . In contrast, in the current study, effects on cognitive impairment were examined in a CORT‐treated model.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…However, there is no effective treatment available to cure this dreadful disease. Though recent some extracts/compounds of plants were reported to anti-amnestic efficacies [ 34 , 35 ], effective anti-amnestic agents have not been discovered yet.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the increments of both neurite-bearing cells and neurite length were notably subdued in MS-and AS-treated cells when ERK1/2 was inhibited. Several reports have suggested the possibility of triterpenoid and steroidal glycosides activating TrkA receptor and subsequently stimulating ERK1/2 signal transduction in neuronal cells [28][29][30].…”
Section: Discussionmentioning
confidence: 99%